Renewal revisited: a new study of the late-Ming Buddhism - Berezkin, Rostislav (Studies in Chinese Religions, 2020)
This piece discusses the new study of the renewal of Buddhism in China in the late-sixteenth and early-seventeenth centuries: Thriving in Crisis: Buddhism and Political Disruption in China, 1522-1620 by Dewei Zhang. The book under review approaches this historical phenomenon from the religio-political perspective with the use of modern Western methodology and revises some conclusions of previous studies on this topic. The book represents the most detailed and in-depth research on the late-Ming revival of Buddhism in Western languages. This review underlines major contributions of this study in the fields of Chinese history, religion, and cultural studies, and demonstrates its special features in comparison with the preceding research works (both in English and Chinese). Zhang’s book uncovers complex relations between state authorities, different social groups, and Buddhist institutions in China in the late-Ming period.